Preparation method of ammonium sulfate spherical crystal and ammonium sulfate

The preparation of ammonium sulfate spherical crystals by cooling and heating under stirring conditions has been solved, and the preparation of ammonium sulfate spherical crystals in the prior art has been achieved, and a product with high fluidity, anti-caking and uniform particles has been achieved. The process is simple, environmentally friendly, economy.

CN119390090APending Publication Date: 2025-02-07TIANJIN UNIV +1

Patent Information

Application Number
CN202411410121.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare ammonium sulfate spherical crystals with high fluidity, anti-caking and uniform particles, and the process is complex, the cost is high, and the product quality is poor.

Method used

The ammonium sulfate solution at 70-80°C was cooled to 65-68°C under stirring conditions and added ammonium sulfate seeds, and continued to cool to 1-15°C, and then heated to 20-25°C under stirring conditions to make the crystal surface The edges and angles were dissolved, and stirring continued for 0.5 to 5 hours to obtain spherical particles of ammonium sulfate.

Benefits of technology

It realizes the efficient preparation of ammonium sulfate spherical crystals, the product has tight particles, good fluidity, anti-caking, simple process, green and environmentally friendly, low economic cost, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390090A_ABST
    Figure CN119390090A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of ammonium sulfate spherical crystals and ammonium sulfate. The preparation method of the ammonium sulfate spherical crystal comprises the following steps: (1) under the condition of 500-800r / min, cooling an ammonium sulfate solution at 70-80 DEG C to 65-68 DEG C, adding a seed crystal, and continuously cooling to 1-15 DEG C; and (2) after cooling is finished, heating to 20-25 DEG C under a stirring condition to dissolve edges and corners on the surfaces of the crystals, and continuously stirring for 0.5-5 hours to obtain the ammonium sulfate spherical particles. The preparation process is single in raw material, only water is involved in the solvent, environmental protection is achieved, and the process is simple; the product particles are round, the average particle size is 900-1100 microns, the fluidity is high, the angle of repose is 15-20 degrees, the caking resistance is better, and the economic and equipment cost of industrial subsequent treatment is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical engineering industrial crystallization, and particularly relates to a preparation method of spherical ammonium sulfate crystals and ammonium sulfate. Background Art

[0002] Ammonium sulfate (Ammonium Sulphate, (NH4)2SO4, CAS Registry No. 7783-20-2), referred to as ammonium sulfate, has a density of 1.769 g / cm3. In addition to nitrogen, ammonium sulfate also contains 25% sulfur, and is also an important sulfur fertilizer. Ammonium sulfate is a white orthorhombic crystal. If the product is mixed with impurities, it will be yellow or gray. It is easily soluble in water, but insoluble in alcohol, acetone and chlorine. When mixed with alkaline substances, it will release ammonia gas. Wet ammonium sulfate is corrosive to both steel and water. The decomposition temperature of ammonium sulfate is 280°C, and the released ammonia gas will become acidic ammonium sulfate NH4HSO4. The solubility of ammonium sulfate at 20°C is 70%, and it reacts neutrally in water. Since free acid is often present in the product, it is also slightly acidic. Ammonium sulfate is mainly used as nitrogen fertilizer in agriculture. Its advantage is that it has relatively low hygroscopicity and has excellent physical properties and chemical stability compared with ammonium nitrate and ammonium carbonate. It is a quick-acting fertilizer and a good biological fertilizer. It reacts acidically in the soil and is suitable for alkaline soil and carbonaceous soil. In addition to nitrogen, ammonium sulfate also contains sulfur, which is extremely beneficial to crops.

[0003] At present, the ammonium sulfate produced industrially is mostly fine grains, and the disadvantages of easy agglomeration and poor fluidity limit the application of ammonium sulfate. Due to the high fluidity, stability, particle uniformity and good anti-caking performance of spherical crystals, the preparation of ammonium sulfate spherical particles can well improve product quality. However, the current research on ammonium sulfate products is mostly focused on the preparation of large particle products, and there is little research on the crystal habit of ammonium sulfate. Suitable processes can significantly improve the crystal habit of the product, thereby improving the tap density and fluidity of the product, and ultimately affecting the subsequent use of ammonium sulfate. CN104903236A proposes a method for ammonium sulfate crystallization, but the method is complicated, costly, and the final product quality is poor.

[0004] Therefore, finding a method for preparing spherical ammonium sulfate crystals that is efficient, green, has uniform particles, good fluidity, is anti-caking and can be industrialized remains an unsolved problem in the prior art. Summary of the invention

[0005] The first aspect of the present application provides a method for preparing spherical ammonium sulfate crystals, the preparation method comprising the following steps:

[0006] (1) Under stirring conditions, cool the ammonium sulfate solution at 70-80° C. to 65-68° C., add seed crystals, and continue to cool to 1-15° C.;

[0007] (2) After cooling, the temperature is raised to 20-25° C. under stirring to dissolve the edges and corners on the crystal surface. Stirring is continued for 0.5-5 h to obtain spherical ammonium sulfate particles.

[0008] In some optional embodiments of the present application, the concentration of the solute in the ammonium sulfate solution in step (1) is 40-45 wt %.

[0009] In some optional embodiments of the present application, the stirring rate in step (1) is 500-800 r / min.

[0010] In some optional embodiments of the present application, 4. The method for preparing spherical ammonium sulfate crystals according to claim 1 is characterized in that the cooling rate in step (1) is 5°C to 20°C / h.

[0011] In some optional embodiments of the present application, the amount of seed crystals added is 1 to 8 wt % of the mass of ammonium sulfate in the ammonium sulfate solution, and the particle size of the added seed crystals is 40 to 100 meshes.

[0012] In some optional embodiments of the present application, the stirring rate is 500-800 r / min.

[0013] In some optional embodiments of the present application, the heating rate in step (2) is 2°C to 10°C / h.

[0014] In some optional embodiments of the present application, the obtained product is sequentially subjected to solid-liquid separation, washing and drying.

[0015] In some optional embodiments of the present application, the method of solid-liquid separation is vacuum filtration.

[0016] In some optional embodiments of the present application, the cleaning is performed with ethanol for 3 to 5 times.

[0017] In some optional embodiments of the present application, the drying conditions are normal pressure, temperature 25-55° C., and drying time 12-48 hours.

[0018] The second aspect of the application provides ammonium sulfate prepared by the method for preparing spherical ammonium sulfate crystals according to the first aspect of the application.

[0019] In some optional embodiments of the present application, the repose angle is between 15° and 20°.

[0020] In order to overcome the defects of the existing ammonium sulfate product preparation method, the present invention provides a method for preparing spherical ammonium sulfate crystals by utilizing crystal abrasion and dissolution. The prepared product has compact particles, good fluidity, anti-caking, simple process and is green and environmentally friendly.

[0021] The technical solution of the embodiment of the present application is as follows:

[0022] (1) Under stirring conditions, cool an ammonium sulfate solution at 70 to 80°C (e.g., 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc.) to 65 to 68°C (e.g., 65°C, 66°C, 67°C, 68°C, etc.), add ammonium sulfate seed crystals, and continue to cool to 1 to 15°C (e.g., 1°C, 3°C, 5°C, 7°C, 10°C, 12°C, 15°C, etc.)

[0023] (2) After the cooling is completed, the temperature is raised to 20-25° C. (e.g., 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., etc.) under stirring, and stirring is continued for 0.5-5 h (e.g., 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, etc.) to obtain spherical ammonium sulfate crystals.

[0024] The concentration of the solute in the ammonium sulfate solution in step (1) is 40-45wt% (e.g., 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, etc.), preferably 42-44wt%;

[0025] The particle size of the ammonium sulfate seed added in step (1) is 40-100 mesh (e.g., 40 mesh, 50 mesh, 60 mesh, 80 mesh, 100 mesh, etc.), preferably 60-80 mesh;

[0026] The amount of ammonium sulfate seed crystals added in step (1) is 1 to 8 wt% (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc.) of the mass of ammonium sulfate in the ammonium sulfate solution, preferably 2.5 to 5 wt%;

[0027] In step (1), the stirring rate is 500-800 r / min (e.g., 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min, 800 r / min, etc.), preferably 600-700 r / min;

[0028] In step (1), the cooling rate is 5°C to 20°C / h (e.g., 5°C / h, 8°C / h, 10°C / h, 13°C / h, 15°C / h, 18°C / h, 20°C / h, etc.). When the cooling rate is higher than the limit of the present invention, the crystal nucleation rate will be too fast, resulting in uneven product particle size.

[0029] In step (2), the stirring rate is 500-800 r / min (e.g., 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min, 800 r / min, etc.), preferably 600-700 r / min;

[0030] In step (2), the heating rate is 2°C to 10°C / h (for example, 2°C / h, 3°C / h, 5°C / h, 7°C / h, 8°C / h, 10°C / h, etc.). When the heating rate is lower than the limit of the present invention, the crystal particle size will become smaller; when the heating rate is higher than the limit of the present invention, the crystal sphericity will be too low.

[0031] Step (2) further comprises performing solid-liquid separation, washing and drying on the mixture obtained after crystal growing;

[0032] The method of solid-liquid separation is filtration.

[0033] Cleaning is done by washing with ethanol 3 to 5 times.

[0034] The drying conditions are normal pressure, temperature 25-55°C (for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, etc.), and drying time 12-48h (for example, 12h, 20h, 24h, 36h, 40h, 48h, etc.).

[0035] The spherical ammonium sulfate product has round particles, good fluidity, and an angle of repose between 15° and 20° (e.g. 15°, 16°, 17°, 18°, 19°, 20°, etc.). The test standard for the angle of repose is GB / T11986-1989.

[0036] Due to the narrow metastable zone of ammonium sulfate and the high hardness of the crystals, conventional rough growth and spherical agglomeration are not suitable for the development of its spherical crystallization process. Rough growth needs to be maintained at a high degree of supersaturation, and the spherical agglomeration process has obvious limitations, often involving dangerous and expensive organic solvents, leading to environmental pollution. The ionic bonds in ionic crystals are stronger than the hydrogen bonds between organic molecules, which makes the crystals harder and therefore not easy to break under high stirring conditions. During the crystal dissolution process, the edges and corners of the ammonium sulfate crystals are more easily dissolved, and because the dissolution rate of the crystals is continuous in space, this causes one face of the crystal to be round and the three-dimensional plane to be spherical. In addition, stirring causes random movement of the fluid, resulting in irregular collisions between the crystals, the crystallizer, and the impeller. The abrasive effect of stirring on the crystals is mainly at the corners, and long-term high-speed stirring will cause the ammonium sulfate crystals to become round. Therefore, the development of the ammonium sulfate spherical crystallization process is achieved by abrasion and dissolution, and the abrasion and dissolution processes are designed to be stable and controllable to obtain spherical ammonium sulfate crystals with compact particles.

[0037] The present invention has the following beneficial effects:

[0038] a) The present invention adopts a one-step heating process to obtain spherical ammonium sulfate crystals. Compared with the traditional granulation process, it has the advantages of high efficiency, simple process, no auxiliary materials, and low energy consumption.

[0039] b) The entire process of the present invention uses only water as a solvent, is green and environmentally friendly, has a single raw material, a simple process, can be industrialized, and has low economic cost.

[0040] c) The spherical particles obtained by the present invention have excellent fluidity and anti-caking properties, which greatly reduces the economic and equipment costs of industrial subsequent treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a stereomicroscope photograph of spherical ammonium sulfate crystals in the embodiment of the present application, with a scale of 1 mm. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0043] [Example 1]:

[0044] (1) At 75° C., a solution with an ammonium sulfate concentration of 42 wt % was prepared, the temperature was lowered to 67° C., and ammonium sulfate seeds with a particle size of 50 mesh and a mass percentage of 5 wt % of the ammonium sulfate were added. The solution was further cooled to 5° C. at a cooling rate of 10° C. / h, and the stirring blade speed was 700 r / min.

[0045] (2) After cooling, the solution was heated to 20°C at a rate of 5°C / h to dissolve the edges and corners on the crystal surface. Stirring was continued for 1h at a stirring speed of 700r / min.

[0046] (3) After vacuum filtration, washing with ethanol, and drying at 50° C. at normal pressure for 12 h, spherical ammonium sulfate crystals were obtained.

[0047] See the stereo microscope pictures of the products Figure 1 The obtained spherical ammonium sulfate product particles are round, the average particle size of the spherical particles is 1080μm, and the angle of repose is 15.4°.

[0048] [Example 2]:

[0049] (1) At 70° C., a solution with an ammonium sulfate concentration of 40 wt % was prepared, the temperature was lowered to 67° C., and ammonium sulfate seeds with a particle size of 80 mesh and a mass percentage of 5 wt % of the ammonium sulfate were added. The solution was further cooled to 5° C. at a cooling rate of 10° C. / h, and the stirring speed was 700 r / min.

[0050] (2) After cooling, the solution was heated to 20°C at a rate of 4°C / h to dissolve the edges and corners on the crystal surface. Stirring was continued for 2 h at a stirring speed of 700 r / min.

[0051] (3) After vacuum filtration, washing with ethanol, and drying at 50° C. at normal pressure for 12 h, spherical ammonium sulfate crystals were obtained.

[0052] The average particle size of the obtained spherical particles was 960 μm, and the angle of repose was 17.2°. The test method used was the same as that in Example 1.

[0053] [Example 3]:

[0054] (1) At 70° C., a solution with an ammonium sulfate concentration of 40 wt % was prepared, cooled to 67° C., and ammonium sulfate seeds with a particle size of 80 mesh and a mass percentage of 5 wt % of the ammonium sulfate were added. The solution was further cooled to 5° C. at a cooling rate of 10° C. / h, and the stirring blade speed was 500 r / min.

[0055] (2) After cooling, the solution was heated to 25°C at a rate of 2°C / h to dissolve the edges and corners on the crystal surface. Stirring was continued for 5 h at a stirring speed of 500 r / min.

[0056] (3) After vacuum filtration, washing with ethanol, and drying at 40° C. at normal pressure for 24 h, spherical ammonium sulfate crystals are obtained.

[0057] The average particle size of the obtained spherical particles was 1040 μm, and the angle of repose was 16.8°. The test method used was the same as that in Example 1.

[0058] [Example 4]:

[0059] (1) At 80° C., a solution with an ammonium sulfate concentration of 45 wt % was prepared, the temperature was lowered to 68° C., and ammonium sulfate seeds with a particle size of 40 mesh and a mass percentage of 8 wt % of the ammonium sulfate were added. The solution was further cooled to 5° C. at a cooling rate of 20° C. / h, and the stirring blade speed was 800 r / min.

[0060] (2) After cooling, the solution was heated to 25°C at a rate of 2°C / h to dissolve the edges and corners on the crystal surface. Stirring was continued for 5 h at a stirring speed of 800 r / min.

[0061] (3) After vacuum filtration, washing with ethanol, and drying at 40° C. at normal pressure for 24 h, spherical ammonium sulfate crystals are obtained.

[0062] The average particle size of the obtained spherical particles was 900 μm, and the angle of repose was 18.4°. The test method used was the same as that in Example 1.

[0063] [Example 5]:

[0064] (1) At 75° C., a solution with an ammonium sulfate concentration of 42 wt % was prepared, the temperature was lowered to 67° C., and ammonium sulfate seeds with a particle size of 100 mesh and a mass percentage of 1 wt % of the ammonium sulfate were added. The solution was further cooled to 10° C. at a cooling rate of 5° C. / h, and the stirring blade speed was 700 r / min.

[0065] (2) After cooling, the solution was heated to 25°C at a rate of 10°C / h to dissolve the edges and corners on the crystal surface. Stirring was continued for 4 h at a stirring speed of 700 r / min.

[0066] (3) After vacuum filtration, washing with ethanol, and drying at 45° C. at normal pressure for 36 h, spherical ammonium sulfate crystals were obtained.

[0067] The average particle size of the obtained spherical particles was 1030 μm, and the angle of repose was 17.3°. The test method used was the same as that in Example 1.

[0068] [Comparative Example 1]:

[0069] The only difference from Example 1 is that the rotation speed of the stirring paddle is 1000 r / min.

[0070] The average particle size of the obtained spherical particles was 640 μm, and the angle of repose was 24.6°. The test method used was the same as that in Example 1.

[0071] [Comparative Example 2]:

[0072] The only difference from Example 1 is that the cooling rate in step (2) is 30° C. / h.

[0073] The average particle size of the obtained spherical particles was 800 μm, and the angle of repose was 25.8°. The test method used was the same as that in Example 1.

[0074] [Comparative Example 3]:

[0075] The only difference from Example 1 is that after the temperature reduction process is completed, no temperature increase operation is performed.

[0076] The average particle size of the obtained spherical particles was 1070 μm, and the angle of repose was 22.6°. The test method used was the same as that in Example 1.

[0077] The anti-caking performance of the crystalline product is evaluated by an accelerated caking experiment, and the specific steps are as follows: 2 g of ammonium sulfate sample is accurately weighed with an analytical balance and placed in a container and evenly sprayed with an appropriate amount of deionized water. After drying in an oven at 50° C. for 24 hours, the agglomerated ammonium sulfate particles cannot pass through the sieve due to the increased volume, and the particles are screened manually. The agglomeration ratio is estimated from the ratio of agglomerated particles to the total particle mass. The following table (Table 1) shows the agglomeration rates of ammonium sulfate products prepared in different embodiments and comparative examples.

[0078] Table 1. Agglomeration rate of ammonium sulfate products obtained in different embodiments and comparative examples

[0079]

[0080] By comparing Example 1 with Comparative Example 1, it can be seen that when the stirring rate is higher than the specified range of the present invention, the particle performance of the product is poor. This is because when the stirring rate is too high, the collision between particles is intensified, the secondary nucleation is serious, and the wear between particles is intensified, which leads to the failure to obtain a product with good particle performance.

[0081] By comparing Example 1 with Comparative Example 2, it can be seen that when the cooling rate is higher than the specified range of the present invention, the particle size of the product is small and the quality is poor. This is because the cooling rate is too fast and the supersaturation is high, resulting in explosive nucleation, which leads to small particle size of the obtained product, poor product quality, and easy agglomeration.

[0082] By comparing Example 1 with Comparative Example 3, it can be seen that the sphericity of the product is poor in the experiment without heating operation. This is because the hardness of ammonium sulfate crystals is relatively large, and the degree of wear on the crystals by simple stirring is limited, while heating leads to increased solubility, and the dissolution rate of the edges and corners of ammonium sulfate crystals is higher than the dissolution rate of the faces. During the heating process, the crystals gradually dissolve and tend to be spherical, and finally a product with good sphericity is obtained. Since the contact area between block particles is large and the contact area between spherical particles is small, block particles are more likely to agglomerate.

[0083] The present invention discloses and proposes a method for preparing spherical ammonium sulfate crystals. Those skilled in the art can refer to the content of this article and appropriately change the stirring rate, heating method, cooling end temperature, cooling rate, heating rate and other links to achieve the method. The method of the present invention has been described through a preferred embodiment, and relevant technical personnel can obviously modify or appropriately change and combine the methods and products described herein without departing from the content, spirit and scope of the present invention to achieve the technology of the present invention. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A method for preparing spherical ammonium sulfate crystals, characterized in that: The preparation method comprises the following steps: (1) Under stirring conditions, cool the ammonium sulfate solution at 70-80° C. to 65-68° C., add seed crystals, and continue to cool to 1-15° C.; (2) After cooling, the temperature is raised to 20-25° C. under stirring to dissolve the edges and corners on the crystal surface. Stirring is continued for 0.5-5 h to obtain spherical ammonium sulfate particles.

2. The preparation method of spherical ammonium sulfate crystals as claimed in claim 1, characterized in that: The concentration of the solute in the ammonium sulfate solution in step (1) is 40-45 wt%.

3. The preparation method of ammonium sulfate spherical crystals as claimed in claim 1, characterized in that, The stirring rate in step (1) is 500-800 r / min.

4. The preparation method of spherical ammonium sulfate crystals as claimed in claim 1, characterized in that: The cooling rate in step (1) is 5°C to 20°C / h.

5. The preparation method of spherical ammonium sulfate crystals as claimed in claim 1, characterized in that, The amount of seed crystals added in the step (1) is 1 to 8 wt % of the mass of ammonium sulfate in the ammonium sulfate solution, and the particle size of the seed crystals added is 40 to 100 meshes.

6. The preparation method of ammonium sulfate spherical crystals as claimed in claim 1, characterized in that: The stirring rate in step (2) is 500-800 r / min.

7. The method for preparing spherical ammonium sulfate crystals according to claim 1, wherein: The heating rate in step (2) is 2°C to 10°C / h.

8. The method for preparing spherical ammonium sulfate crystals according to claim 1, wherein: The preparation method further comprises sequentially performing solid-liquid separation, washing and drying on the obtained product; Preferably, the solid-liquid separation method is suction filtration; Preferably, the cleaning is performed by washing with ethanol 3 to 5 times; Preferably, the drying conditions are normal pressure, temperature 25-55° C., and drying time 12-48 hours.

9. The method for preparing spherical ammonium sulfate crystals as described in any one of claims 1 to 8 prepares ammonium sulfate.

10. Ammonium sulfate according to claim 9, characterized in that The average particle size of the ammonium sulfate is between 900 and 1100 μm, and the angle of repose is between 15° and 20°.

Citation Information

Patent Citations

  • Process and apparatus for producing ammonium sulfate crystals

    CN104903236A

Cited By

  • Ammonium sulfate crystallization device and ammonium sulfate crystallization manufacturing method

    CN122032136A

  • Apparatus for crystallizing ammonium sulfate and method for crystallizing ammonium sulfate

    CN122032136B